Seasonal distribution and cercarial shedding of Bulinus spp. snails: Implications for urogenital schistosomiasis control in the Simiyu Region, northwestern Tanzania - Nyanda C. Justine; Humphrey D. Mazigo; Antje Fuss; Bonnie L. Webster; Eveline T. Konje; Klaus Brehm; Andreas Mueller (Current Research in Parasitology and Vector-Borne Diseases)
Urogenital schistosomiasis is a neglected tropical disease of significant public health concern caused by the trematode species Schistosoma haematobium. Its transmission is localised and heterogeneous, with seasonal occurrences in Tanzania primarily facilitated by Bulinus spp. snails, which serve as intermediate hosts. To plan effective, data-driven control measures, it is crucial to understand the epidemiology of schistosomes in these snails. This study aimed to investigate the seasonal distribution, abundance, and Schistosoma spp. infections (assessed via cercarial emergence) in Bulinus spp. snails in two districts, Maswa and Meatu, in the Simiyu Region of Tanzania. Malacological surveys were conducted at 90 sites in total, comprising sites in 35 rivers, 32 ponds, and 23 branching streams. Each study site was sampled once during the rainy season and once during the dry season. Snails were collected using a standard scoop- and handpicking technique by two people for 15 min at each site. The collected snails were morphologically identified and subjected to a cercarial emergence experiment. Water physicochemical characteristics were recorded simultaneously with snail collection using a portable multiparameter water meter. The data were analysed using STATA v. 17. A total of 4997 Bulinus spp. snails were collected from 90 sites in the two districts. Of these, 91.4% (95% CI: 90.5–92.1%) were morphologically identified as Bulinus nasutus and 8.6% (95% CI: 7.8–9.4%) were identified as Bulinus globosus. Bulinus spp. snail abundance was almost evenly distributed across seasons, with 50.4% (95% CI: 48.9–51.7%) collected during the dry season and 49.6% (95% CI: 48.2–51.0%) collected during the rainy season. Water temperature and salinity were significantly negatively correlated with snail abundance (both P < 0.001). Schistosoma spp. cercarial emergence followed a seasonal pattern and was significantly higher during the rainy season (P = 0.005). Our findings underscore that B. nasutus was the most abundant freshwater snail distributed at nearly all the study sites during the rainy and dry seasons. Therefore, appropriate snail control strategies are recommended to complement ongoing schistosomiasis control strategies in the Simiyu Region.